The villainous stage : crime plays on Broadway and in the West End - Lachman, Marvin (McFarland & Company, Inc., Publishers, 2014)
"Live theatre was once the main entertainment medium in the U.S. and the United Kingdom. The preeminent dramatists and actors of the day wrote and performed in plays in which crime was a major plot element. This remains true today, especially with the longest-running shows such as The Phantom of the Opera, Les Miserables and Sweeney Todd"--